Dombra discourse in the modern kazakh audience (Journal of Philosophy Culture and Political Science, 2022)
Dombra, the most common musical instrument of the Kazakh people, is now the main cultural heritage of the nation. However, the appearance of the instrument, which has been preserved since ancient times, is changing today. This can be seen in the growing number of conflicting opinions about dombra today. However, the question of what is the flow of these opinions and what is the real perception of dombra by modern Kazakhs is becoming an urgent question. In this regard, the study aims to conduct a study of the contradictions and acceptance of dombra in Kazakhstan. To achieve this goal, a qualitative and quantitative analysis of the content of several portals and social networks in the internet space was carried out.As a result of the study, four different views on dombra, which often occur in society, were grouped: opinions linking the place of Dombra with the old Kazakh faith; the recognition of Dombra only as a musical instrument and as a cultural heritage of the Kazakh people; positions that deny the fact that Dombra contradicts the Islamic religion and its current use; information that confirms that Dombra is not contrary to Islamic tradition, recognizing it as a National Instrument. The level and reasons for the conflict of grouped opinions were identified and analyzed separately.The research work contributes to the formation of a hypothetical base of dombra discourse in the Kazakh audience in Kazakhstan. Keywords: Dombra, Kazakh, Haram, shaman, identification